Dorian Gieseler Greenbaum, The Daimon in Hellenistic Astrology: Origins and Influence. (14th February 2019) - Beck, Roger
Abstract : Dorian Gieseler Greenbaum, The Daimon in Hellenistic Astrology: Origins and Influence (Leiden: Brill, 2015), xiii + 573 pp., €186.00 (hbk), ISBN: 978-9004306-20-2.